Laboratory-based assessment of the Underwater Laser Scanner ULi - E. Heffner; A. L. Walter; A. Scheider; H. Sternberg (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Optical measurement methods are widely used for precise and high-resolution underwater monitoring applications, however, remain limited in range as they are strongly affected by visibility. Through enhancements in laser technology, green LiDAR systems expand the range in the underwater domain under favourable conditions. The Underwater LiDAR System (ULi), recently developed by the Fraunhofer Institute for Physical Measurement Techniques (IPM), is a Time-of-Flight (ToF) laser scanner optimized for underwater operation. This paper assesses the actual performance of ULi under varying environmental conditions in controlled laboratory setups. We present the results of static scans on different test objects like a Böhler-Star, spheres and metal plates at different distances and varying turbidity levels. Through repetitive range measurements on a metal plate range precision of ULi is evaluated to be 1.95 mm and ULi achieves a mean relative range accuracy of 6.01 mm. Additionally, we demonstrate that objects like small shells and water plants can be clearly identified in low turbid water.